Renewed Prospects for Organic Photovoltaics - Zhang, Guichuan; Lin, Francis R.; Qi, Feng; Heumüller, Thomas; Distler, Andreas; Egelhaaf, Hans-Joachim; Li, Ning; Chow, Philip C. Y.; Brabec, Christoph J.; Jen, Alex K.-Y.; Yip, Hin-Lap (Chemical reviews, 2022)
Organic photovoltaics (OPVs) have progressed steadily through three stages of photoactive materials development: (i) use of poly(3-hexylthiophene) and fullerene-based acceptors (FAs) for optimizing bulk heterojunctions; (ii) development of new donors to better match with FAs; (iii) development of non-fullerene acceptors (NFAs). The development and application of NFAs with an A–D–A configuration (where A = acceptor and D = donor) has enabled devices to have efficient charge generation and small energy losses (E loss < 0.6 eV), resulting in substantially higher power conversion efficiencies (PCEs) than FA-based devices. The discovery of Y6-type acceptors (Y6 = 2,2′-((2Z,2′Z)-((12,13-bis(2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]-thiadiazolo[3,4-e]-thieno[2″,3″:4′,5′]thieno-[2′,3′:4,5]pyrrolo-[3,2-g]thieno-[2′,3′:4,5]thieno-[3,2-b]indole-2,10-diyl)bis(methanylylidene))bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononitrile) with an A–DA′ D–A configuration has further propelled the PCEs to go beyond 15% due to smaller E loss values (∼0.5 eV) and higher external quantum efficiencies. Subsequently, the PCEs of Y6-series single-junction devices have increased to >19% and may soon approach 20%. This review provides an update of recent progress of OPV in the following aspects: developments of novel NFAs and donors, understanding of the structure–property relationships and underlying mechanisms of state-of-the-art OPVs, and tasks underpinning the commercialization of OPVs, such as device stability, module development, potential applications, and high-throughput manufacturing. Finally, an outlook and prospects section summarizes the remaining challenges for the further development of OPV technology.